Asuransi Ketenagakerjaan dan Penjaminan Keselamatan Kerja : (Studi PT. Meskom Bengkalis) - Irwani, Agustina; Astuti, Yulia; Purwanto, Muhammad Aji (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2024)
Work safety refers to the physiological-physical and psychological conditions of workers resulting from the work environment provided by the company. Islam also requires a company to provide safety guarantees to protect and maintain the health and safety of workers. The research method used in this journal is a research library study which is a library study, meaning that information is collected through the use of library sources. Work safety is the protection of workers to guarantee the basic rights of workers/laborers and guarantee equality of opportunity and treatment without discrimination on any basis to realize the welfare of workers/laborers and their families while still paying attention to developments in the business world. Objectives and factors of occupational safety. The essence and objectives of occupational safety greatly influence the work effectiveness of the workforce and also influence the production efficiency of a company, thereby influencing the level of productivity achieved.